1992
DOI: 10.1152/jappl.1992.73.2.s166
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary oxytocin and vasopressin content of rats flown on COSMOS 2044

Abstract: Preliminary studies in rats (COSMOS 1887) suggested that levels of posterior pituitary hormones were reduced by exposure to spaceflight. To confirm these preliminary findings, we obtained pituitary tissue from rats flown for 14 days on COSMOS 2044. Posterior pituitary content of oxytocin (OT) and vasopressin (VP) were measured in these tissues as well as those from ground-based controls. The synchronous control group had feeding and lighting schedules synchronized to those in the spacecraft and were maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, it was shown that AVP and ANP, respectively, have stimulatory and inhibitory effects on the choroidal CSF secretion (23,29). In rats, adaptation to spaceflight induces decreases in hypothalamic (6) and neurohypophyseal AVP content (13) and increases in choroidal NP receptor number (12) and cGMP content (C. Carcenac, S. Herbuté, C. Masseguin, L. Mani-Ponset, D. Maurel, R. Briggs, A. Gü ell, and J. Gabrion, unpublished observations). It is important to note that cGMP is produced in choroidal cells after activation of the guanylate cyclase domain of the biologically active NP receptors (30), particularly when the CSF production is reduced (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that AVP and ANP, respectively, have stimulatory and inhibitory effects on the choroidal CSF secretion (23,29). In rats, adaptation to spaceflight induces decreases in hypothalamic (6) and neurohypophyseal AVP content (13) and increases in choroidal NP receptor number (12) and cGMP content (C. Carcenac, S. Herbuté, C. Masseguin, L. Mani-Ponset, D. Maurel, R. Briggs, A. Gü ell, and J. Gabrion, unpublished observations). It is important to note that cGMP is produced in choroidal cells after activation of the guanylate cyclase domain of the biologically active NP receptors (30), particularly when the CSF production is reduced (29).…”
Section: Discussionmentioning
confidence: 99%